Odpowiedzi

Najlepsza Odpowiedź!
2009-11-30T16:33:45+01:00
1. -3(2x+7)=-3x-21
2. -4(a-b)=-4a+4b
3. 7(5-c)=35-7c
4. -12(-⅓+z)=4-12z
5. a(a-b)=a²-ab
6. 2a(3a-2)=6a²-4a
7. -x(5y+x)=-5x-x²
8. -2x(-2x-3+y)=4x²+6x-2xy
9. (2x+6):2=x+3
10.(3x-12):3=x-4
11.(4x-8):(-2)=-2x+4
12.(10x+15):5=2x+3
2 3 2
2009-11-30T16:35:23+01:00
1. -3(2x+7) = -6x - 21
2. -4(a-b) = -4a + 4b
3. 7(5-c)= 35 - 7c
4. -12(-⅓+z)= 4 - 12z
5. a(a-b)= a2 - ab
6. 2a(3a-2)= 6a2 - 4a
7. -x(5y+x)= - 5xy - x2
8. -2x(-2x-3+y)= 4x2 + 6x - 2xy
9. (2x+6):2= x + 3
10.(3x-12):3= x - 4
11.(4x-8):(-2)= -2x + 4
12.(10x+15):5= 2x + 3
1 5 1